2010
DOI: 10.1021/om100810t
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Addition of Ethyl Iodide to a Dimethylplatinum(II) Complex: Unusually Large Kinetic Isotope Effects and Their Transition-State Implications

Abstract: The mechanism of oxidative addition of ethyl iodide to [PtMe 2 (2,2 0 -bipyridine)], 1, has been investigated by product analysis and by study of secondary deuterium kinetic isotope effects (KIEs), using the reagents C 2 H 5 I, C 2 D 5 I, CH 3 CD 2 I, and CD 3 CH 2 I. The reactions in acetone and benzene give [PtIMe 2 Et(bipy)], mostly as the product of trans oxidative addition, but with some of the isomeric product of cis oxidative addition and some [PtIMe 3 (bipy)], resulting from methyl group transfer. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 68 publications
6
27
0
Order By: Relevance
“…So these results in general are consistent with our recent studies indicating that nature of the diimine (or its substituted version) peripheral ligands (steric and electronic) may only have a mild influence on the KIE values [13e16]. We, however, have lately reported that KIE values in reactions of the Pt(II) complex [PtMe 2 (2,2 0 -bipyridine)] with CH 2 RX reagents (in which R ¼ H [14], CH 3 [13], or Ph [16]) are significantly dependent on R and a high value is obtained when R is CH 3 or Ph. The latter cases have been described [13,16] as the presence of bulkier alkyl halides and creation of more room for the CaÀH(D) out-of-plane bending vibration [34].…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…So these results in general are consistent with our recent studies indicating that nature of the diimine (or its substituted version) peripheral ligands (steric and electronic) may only have a mild influence on the KIE values [13e16]. We, however, have lately reported that KIE values in reactions of the Pt(II) complex [PtMe 2 (2,2 0 -bipyridine)] with CH 2 RX reagents (in which R ¼ H [14], CH 3 [13], or Ph [16]) are significantly dependent on R and a high value is obtained when R is CH 3 or Ph. The latter cases have been described [13,16] as the presence of bulkier alkyl halides and creation of more room for the CaÀH(D) out-of-plane bending vibration [34].…”
Section: Resultssupporting
confidence: 91%
“…The reactions of many platinum(II) complexes with MeI have been extensively investigated both theoretically and experimentally [6,7,17,22] and in all cases, an S N 2 mechanism has been suggested. Operation of S N 2 mechanism in oxidative addition of alky halides to some organoplatinum(II) complexes has also been confirmed by secondary deuterium KIE study involving the reaction of MeI/CD 3 I or C 2 H 5 I/C 2 D 5 I [13,15].…”
Section: Kinetic Isotope Effect (Kie) Studymentioning
confidence: 69%
See 1 more Smart Citation
“…Alternatively, M can be isomerised by pseudo-rotation to give N [22], which can also be trapped by iodide to give 3. We suggest that formation of the thermodynamic isomer 3 is favoured over the kinetic isomer 2 as in former the more sterically demanding L ligands are situated in the "axial" positions as compared with the latter in which they are located in the "equatorial" position.…”
Section: Kinetic and Mechanism Of The Reaction Of Complexes 1 With Meimentioning
confidence: 99%
“…[1,6,[19][20][21][22][23][24][25][26][27] This involves nucleophilic substitution of halide by Pt complex to form a Pt-C bond, followed by subsequent coordination of halide to form a six-coordinate octahedral alkyl product. It is interesting to compare the behaviours of RCH 2 Br (R = CH 3 , Ph and PhCH 2 ) in their oxidative addition reactions with the organoplatinum(II) complex 1a with an emphasis on the differences between the effect of the R group of alkyl halides.…”
Section: Dft Studymentioning
confidence: 99%